Klinische Prüfungen mit Arzneimitteln in der Schwangerschaft - Knop, Sonja (Universitätsverlag Göttingen, 2015)
The clinical trial on medicinal products stands in the area of conflict between important scientific progress in favour of future patients on the one hand and the necessary protection of human subjects on the other hand. This conflict grows more acute when vulnerable persons - like pregnant women - are included in medical research. Whereas there are specific regulations for minors or incapacitated persons in the German Medicinal Products Act, legal regulations for the inclusion of pregnant women are missing. Based on this uncertain legal situation solutions are developed, which will show a way out of the dilemma. Insofar as the applicable law does not provide a handle for this problem, a need for reform is shown.